Delivery of Iron Oxide Nanoparticles into Primordial Germ Cells in Sturgeon - Abdul Rasheed Baloch; Michaela Fučíková; Marek Rodina; Brian Metscher; Tomáš Tichopád; Mujahid Ali Shah; Roman Franěk; Martin Pšenička (Biomolecules, 2019)
Nanoparticles are finding increasing applications in diagnostics, imaging and therapeutics in medicine. Iron oxide nanoparticles (IONs) have received significant interest of scientific community due to their distinctive properties. For the first time, we have delivered IONs into germ cells in any species. Our results showed that sturgeon primordial germ cells (PGCs) delivered with IONs could be detected until seven days post fertilization (dpf) under fluorescent microscope and at 22 dpf by micro-CT. Delivery of IONs into cells could be helpful for studying germ cell biology and the improvement of germ cell-based bio-technologies as isolation of PGCs using magnetic activated cell sorting or application of hyperthermia for a host sterilization purpose. Intriguingly, in our study, we did not find any toxic effects of IONs on the survival and hatching rates of sturgeon embryos when compared with embryos injected with FITC-dextran only.